Factors Predicting Self-management for Stroke Prevention among Older Adults with Hypertension - Ruangchaithaweesuk, Kunnicha; Charoenchit, Lalin; Tipkanjanaraykha, Kitsanaporn; Laochai, Wiwat (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Stroke among older adults is mainly caused by hypertension, especially in those with poorly controlled blood pressure. This study aimed to explore selected factors for predicting self-management for stroke prevention in older adults with hypertension. Methods The participants were older adults diagnosed with hypertension. Simple random sampling was used to select 131 patients for the study. Research instruments were 1) Personal Information Questionnaire, 2) Thai Health Literacy Scale, 3) Stroke Knowledge Questionnaire, and 4) Self-Management for Stroke Prevention Questionnaire. The reliability of instruments 2–4, assessed using Cronbach’s alpha coefficient, was .93, .92, and .79, respectively. The data were analyzed by using enter multiple regression analysis. Results Self-management for stroke prevention was at a high level, with a mean score of 129.34 (SD = 13.11). Knowledge of stroke was also at a high level, with a mean score of 75.49 (SD = 9.37). Health literacy was at a sufficient level, with a mean score of 180.72 (SD = 23.11). Furthermore, health literacy and stroke knowledge were significant predictors of self-management for stroke prevention at the .05 level, jointly explaining 48.1% of the variance (R² = .481). Conclusion and Recommendation Health literacy and stroke knowledge jointly predicted self-management for stroke prevention among older adults with hypertension. Therefore, healthcare teams should develop programs aimed at enhancing health literacy and stroke-related knowledge in older adults with hypertension to strengthen their self-management capacity for stroke prevention.